Perbedaan Pengaruh Fungsi Guru (Guru Bidang Studi dengan Guru Kelas) terhadap Hasil Belajar Matematika Ditinjau dari Tingkat IQ Siswa - Nurhayati Nurhayati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2014)
The aim of the study was to analyze differences in the influence function of teachers (between classroom teachers with subject teachers ) and the IQ level of the mathematics learning outcomes. This research was conducted at the fifth grade elementary school students in the district Kramat Jati. The sample used in this study consisted of 10 elementary schools, both public and private as many as 352 students and were selected by cluster sampling. Normality Tests performed using Liliefors test with the results of several different groups. Where data is normally categorized Testing homogeneity with the Bartlet test results data used is homogeneous. Research hypothesis testing using 2 way ANOVA, with the calculation that the learning outcomes of students who are taught mathematics by teachers of better than students taught by classroom teachers, math learning outcomes of students who have a high IQ level is better than the students who have a low IQ level, there was an interaction effect between the teacher and the function of the IQ level of mathematics learning outcomes of primary school students in the District Kramat Jati.